English teachers' attitudes concerning their use of L1 in the classrooms : an exploratory sequential study - Campos Morales, Meilin Alejandra 1997-; Chaves González, Brayner Snaider 1999-; Leiva Guerrero, Alisson María 1996-; Quirós Montenegro, Jennifer María 1992-; Sevilla Morales, Henry 1986- ([San Ramón, Alajuela, Costa Rica], 2022)
This study aimed to explore what common attitudes in-service MEP English teachers hold towards their own use of L1 in the classroom by conducting an exploratory sequential study in the Western zone of Costa Rica (San Ramón, Palmares, Sarchí, Grecia, and Naranjo). The literature reviewed expounds on the lack of evidence in Costa Rica to acknowledge the attitudes that arise in teachers while using the resource of L1 further to advance students' progress in their L2 learning process. A QUAL-Quan research design was used for this study. Four MEP English teachers comprised the qualitative sample, which consisted of a semi-structured interview and a post-interview reflection form. After administering these instruments, twenty-two educators collaborated in the quantitative stage, which involved the administration of a survey, giving a final total of twenty-six informants. The four qualitative interviews were handled during Zoom sessions, while the post interview reflection and survey were run using Google Forms documents. Some of the participants were contacted directly at MEP institutions, while others were reached via social media. In general, findings indicate that the majority of the participants acknowledged using Spanish in their classes, which was generally linked with the attitude of empathy toward students. Results also suggest that, according to the participants' beliefs, making use of L1 works as a tool for teaching-learning purposes, which facilitates comprehension, benefits class management, promotes a sense of confidence, and decreases levels of frustration, anxiety, and stress. None of the informants reported to endorse unlimited use of L1; instead, they highlighted that it is paramount to control the amount of L1 employed in order to avoid its overuse.
Tesis (licenciatura en la enseñanza del inglés)--Universidad de Costa Rica. Sede de Occidente. Departamento de Filología, Artes y Letras, 2022
Keywords: PROFESORES DE INGLES -- ACTITUDES -- ALAJUELA (COSTA RICA); EDUCACION BILINGUE; INGLES -- ESTUDIO Y ENSEÑANZA; INGLES -- METODOS DE ENSEÑANZA